CHO oxidation from a CHO gel compared with a drink during exercise - Pfeiffer, B.; Stellingwerff, T.; Zaltas, E.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2010)
Recently, it has been shown that ingestion of solutions with glucose (GLU) and fructose (FRC) leads to 20%-50% higher CHO oxidation rates compared with GLU alone. Although most laboratory studies used solutions to deliver CHO, in practice, athletes often ingest CHO in the form of gels (semisolid). It is currently not known if CHO ingested in the form of a gel is oxidized as effectively as a drink.